Telehealth and Assistive Technology / 847: Intelligent Systems and Robotics 2016
DOI: 10.2316/p.2016.846-007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wearing Whole Body Compression Garments on Cardiovascular Function using ECG Signals

Abstract: The purpose of this study was to examine the effects of wearing whole body compression garments (WBCGs) on cardiovascular function of running trainers. Eight nonathletes (age: 25.1±3.8 years, height: 165.9±8.3 cm; weight: 61.4±13.7 kg) performed an incremental test followed by 30 minutes running on a treadmill, from 6 km.h-1 to 11 km.h-1 with correct size-compression garments (CCGs), undersize-compression garments (UCGs) and non-compression garments (NCGs). During the exercise, electrocardiogram (ECG) signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
4
0
0
Order By: Relevance
“…Moreover, a significant increase in cardiac arrhythmias also associated with the prolongation of QTc [ 18 ]. The current results are consistent with our previous observation suggesting that the pressure of CGs may effect on QTc parameters [ 31 ]. Based on the findings of lower QTc, CGs may have a positive influence on the recovering phase.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, a significant increase in cardiac arrhythmias also associated with the prolongation of QTc [ 18 ]. The current results are consistent with our previous observation suggesting that the pressure of CGs may effect on QTc parameters [ 31 ]. Based on the findings of lower QTc, CGs may have a positive influence on the recovering phase.…”
Section: Discussionsupporting
confidence: 94%
“…The present study investigated a significant lower QTc when using compression garments compared with non-compression garments after a 90-min of recovering time (p < 0.05). Similarly, an earlier study indicated a shorter value of QTc at the end of a running experiment in CGs group [ 31 ]. The previous finding proved that the longer QTc related to the development of atrial fibrillation and incidence of stroke [ 19 ].…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, some previous research indicated a significant development in the risk of cardiac arrhythmias has a relationship with the QTc prolongation [20]. This present finding also is consistent with our previous study concluding that the pressure of CGs may influence on QTc value [28]. As a result, CGs may have positive effects on recovery based on the lower QTc.…”
Section: Discussionsupporting
confidence: 93%
“…This present investigation has shown that wearing CG results in a significant lower QTc after 90-min recovery compared with wearing NCGs (p<0.05). Consistent with this, earlier research has demonstrated shorter corrected QT interval in a group of using CGs at the end of a running test [27]. The longer QTc is associated with an increased incidence of stroke and atrial fibrillation [21].…”
Section: Discussionsupporting
confidence: 54%